ANALISIS TINGKAT PENDAPATAN UTAMA DAN SAMPINGAN PADA RUMAH TANGGA PERIKANAN (RTP) NELAYAN GILLNET DI DESA ASINAN, KECAMATAN BAWEN, KABUPATEN SEMARANG, JAWA TENGAH - Oktaveasmara, Alfian; Bambang, Azis Nur; Yulianto, Taufik (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2013)
A strategy to overcome the lack of income obtained from the primary job as gillnet fishermen, households fishermen in the Asinan village have some alternative jobs such as agricultural labour, construction workers, farming, goat farming, trade, and ranching of fish cages. The purpose of this research was to analyze the level of primary and alternative income gillnet fishermen households in Asinan, Bawen, Semarang and was to determine the technical aspects of gillnet fishing gear which is used by fishermen in Asinan. The research method were descriptive method and case study. The sampling method was census by interviewing 64 fishermen as respondents. The results showed that the average primary income of gillnet fishermen per year was Rp 9,600,063.00 and the average alternative income of gillnet fishermen per year was Rp 7,129,307.00. The maximum average alternative income was Rp 31,734,333.00 per year obtained from trade. The minimum average alternative income was Rp 3,198,890.00 per year obtained from goat farming. Webbing was made from nylon (PA) monofilament with diameter 0.12 mm; length 15 m; mesh size 7.62 cm (3 inches); and height 78.6 cm. The net had 91.44 cm stretched height with 12 of vertical and 400 of horizontal meshes. Hanging ratio value was 0.50 and 0.50 for shortening. Head rope was made from PA monofilament with diameter 0.5 mm, and length 15.3 m per piece. Sinker line was made from PE multifilament with diameter 0.2 mm and length 15 m per piece. The floats were made from water hyacinth material. Sinkers used were made from circular iron wire with 20 gr weight and diameter 7.7 cm. Total sinkers were 100 pieces and mounted on every 20 meshes.